2013
DOI: 10.1056/nejmsa1212321
|View full text |Cite
|
Sign up to set email alerts
|

The Oregon Experiment — Effects of Medicaid on Clinical Outcomes

Abstract: BACKGROUND Despite the imminent expansion of Medicaid coverage for low-income adults, the effects of expanding coverage are unclear. The 2008 Medicaid expansion in Oregon based on lottery drawings from a waiting list provided an opportunity to evaluate these effects. METHODS Approximately 2 years after the lottery, we obtained data from 6387 adults who were randomly selected to be able to apply for Medicaid coverage and 5842 adults who were not selected. Measures included blood-pressure, cholesterol, and gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
813
15

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,002 publications
(875 citation statements)
references
References 13 publications
47
813
15
Order By: Relevance
“…Regarding ex ante moral hazard, the most recent literature has produced some further interesting evidence. The most recent randomized evidence in this sense comes from the Oregon experiment (Baicker et al, 2013), where a group of uninsured low-income adults in…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding ex ante moral hazard, the most recent literature has produced some further interesting evidence. The most recent randomized evidence in this sense comes from the Oregon experiment (Baicker et al, 2013), where a group of uninsured low-income adults in…”
Section: Discussionmentioning
confidence: 99%
“…Since co-payments have not been increased (actually dropped in 2007) and costs of healthcare have been raising constantly, both concerns are still shared among experts from different fields. Indeed, part of these worries were confirmed by the authoritative recent Oregon Experiment (Baicker et al, 2013), where Medicaid has been shown to increase financial protection and accessibility to healthcare services, but with ambiguous impacts on health and healthy behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…First, socioeconomically disadvantaged populations suffer from a great burden of Framingham risk factors. 34,[268][269][270][271][272][273][274] This is an important consideration because it may be possible to use clinical 109 and public health interventions 92 to reduce this burden, thereby narrowing health disparities. Second, social and economic stresses lead to a biological wear and tear, or allostatic stress response, [275][276][277][278][279][280] involving a number of pathways, including stimulation of stress hormones, [280][281][282] inflammation, 283 endothelial dysfunction, thrombosis, vascular hyperreactivity, 270,274,[284][285][286][287] and metabolic disturbances.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Although Massachusetts residents selfreported better health than patients in neighboring states, usage of preventative care in Massachussetts was only slightly greater [9]. In some respects, this is similar to the ''Oregon Experiment,'' which compared the health of residents who obtained Medicaid coverage through a lottery to those who did not; although patients with diabetes in Oregon who received coverage were more likely to get treatment, outcomes overall did not appear to improve [2].…”
Section: N 2006 Massachusetts Becamementioning
confidence: 65%